Pituitary Apoplexy Induced by Anticoagulant Therapy in Patient with AcuteCoronary Syndrome (Indian Journal of Case Reports, 2024)
Pituitary apoplexy, defined as bleeding or infarct on the pituitary gland often occurs in undiagnosed pituitary tu mors . The patient presented to the emergency room with complaints of chest pain in the last four hours. Electrocardiographic (ECG) and laboratory examination results lead to an acute coronary syndrome (ACS) event. Patients were given fondaparinux, aspirin, and clopidogre l. On the four th day of hospitaliz ation, the patient experienced a severe headache, projectile vomiting, and double vision. Radiological examination reveals a pituitary tumors apoplexy. The patient improved after a conservative approach by the surgeon. In conclusion, pituitary tumors may be a relative contraindication to dual antiplatelets and anticoagulants in acute coronary syndromes especially in patients with renal or liver comorbidities.